Tinjauan Literatur Manajemen Risiko Cyber dalam Proyek: Identifikasi, Evaluasi, dan Mitigasi Ancaman - Br Sitorus, Milky Gratia; Maria, Novita; Safa, Yunisa Nur (Jurnal Manajemen Informatika JAMIKA, 2024)
In today's digital era, business projects are increasingly vulnerable to cyber threats, which can result in significant financial and reputational losses. This journal discusses an effective cyber risk management approach for projects, encompassing the identification, evaluation, and mitigation of digital threats. The objective is to provide an overview of risk management in projects. This journal explains how to identify risks by thoroughly analyzing various potential cyber threats, such as malware, phishing, and DDoS attacks that could impact the project. Subsequently, risk evaluation is conducted by assessing the vulnerability and potential impact of each identified threat, using a literature review method. The literature review includes the analysis of data obtained from relevant articles and books on the topic. The final stage involves risk mitigation, which includes developing strategies to reduce or eliminate the impact of threats, such as implementing security controls, providing employee education and training, and developing incident response plans. This study emphasizes the importance of a proactive and holistic approach to cyber risk management to ensure the success and sustainability of projects. The journal aims to provide an overview of risk management in projects, demonstrating that the integration of comprehensive cyber risk management practices can significantly enhance the resilience of projects against digital threats.